2014
DOI: 10.1016/j.jbi.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Formalizing MedDRA to support semantic reasoning on adverse drug reaction terms

Abstract: Although MedDRA has obvious advantages over previous terminologies for coding adverse drug reactions and discovering potential signals using data mining techniques, its terminological organization constrains users to search terms according to predefined categories. Adding formal definitions to MedDRA would allow retrieval of terms according to a case definition that may correspond to novel categories that are not currently available in the terminology. To achieve semantic reasoning with MedDRA, we have associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Narrative summaries, clinical testing, and physician’s diagnoses from MRVs reports were coded according to Medical Dictionary for regulatory Activities (MedDRA) terminology and System Organ Class (SOC) list [56]. …”
Section: Methodsmentioning
confidence: 99%
“…Narrative summaries, clinical testing, and physician’s diagnoses from MRVs reports were coded according to Medical Dictionary for regulatory Activities (MedDRA) terminology and System Organ Class (SOC) list [56]. …”
Section: Methodsmentioning
confidence: 99%
“…Contrary to our previous approach, definitions of parents in MedDRA were no longer inherited by their children to prevent experienced inconsistencies [06].…”
Section: 2mentioning
confidence: 94%
“…In a previous study we proposed to ''ontologize'' MedDRA and described the general process for formalizing MedDRA to support semantic reasoning [06]. Our In step (a), we often observed that a single MedDRA term mapped to several SNOMED-CT concepts although they have different meanings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example " 'duodenum' is_part_of 'upper digestive tract structure' " where 'duodenum' and 'upper digestive tract structure' are body parts, and 'is_part_of' is a semantic relation. We already described the construction of a semantic resource for ADRs, using description logic (DL), named OntoADR [9,10]. OntoADR contains MedDRA terms formally described with SNOMED CT concepts (Systematized Nomenclature of Medicine -Clinical Terms).…”
Section: Introductionmentioning
confidence: 99%